2015
DOI: 10.1063/1.4921224
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetoimpedance biosensor for ferrogel detection: Model system to evaluate properties of natural tissue

Abstract: Development of magnetoresistive thin film sensor for magnetic field sensing applications AIP Conf. Proc. 1512, 30 (2013); 10.1063/1.4790897 FeNi-based magnetic layered nanostructures: Magnetic properties and giant magnetoimpedance FIG. 2. TEM image (a) and PSD (b) of iron oxide MNPs. 193702-2Kurlyandskaya et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
52
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 20 publications
5
52
0
5
Order By: Relevance
“…Those were exhaustively reviewed recently [72]. Among the different materials used, besides wires and ribbons, thin film structures have been demonstrated to be able to detect microparticles in a flowing liquid [73] and nanoparticles embedded in gels (ferrogel) [74]. In these works, the presence of magnetic particles modifies the magnetic permeability on the medium surrounding the MI element, producing the measured changes in the impedance.…”
Section: Brief Survey Of Applicationsmentioning
confidence: 99%
“…Those were exhaustively reviewed recently [72]. Among the different materials used, besides wires and ribbons, thin film structures have been demonstrated to be able to detect microparticles in a flowing liquid [73] and nanoparticles embedded in gels (ferrogel) [74]. In these works, the presence of magnetic particles modifies the magnetic permeability on the medium surrounding the MI element, producing the measured changes in the impedance.…”
Section: Brief Survey Of Applicationsmentioning
confidence: 99%
“…GMI effect in soft magnetic materials seems to be quit promising for applications in the technological area of small magnetic field sensors and magnetic biosensors [2,3]. The idea of a biosensor based on amorphous ribbon is attractive since this would allow construction of a cheap detector with the sensitive element designed as a disposable strip.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the GMI responses in appropriate conditions can be clearly dependent on the presence of the magnetic ferrofluid and the parameters of the driving current [3,6]. The shape or particular geometry of the sensitive element strongly influences the GMI behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAAm is a water soluble biocompatible polymer and it can form chemically cross-linked networks of homogeneous hydrogels with the network density varying in a broad range. The application of PAAm ferrogels as a potential material for biosensors had been demonstrated [15]. The conventional approach in the studies on polyacrylamide ferrogels is focused on their magnetic properties and their response to the applied magnetic field.…”
Section: Introductionmentioning
confidence: 99%